2020
DOI: 10.1080/13880209.2020.1738502
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tanshinone IIA on renin activity protected against osteoporosis in diabetic mice

Abstract: Context: Salvia miltiorrhiza Bge. (Labiatae) (SMB) is applied clinically for management of diabetic osteoporosis in China, and research results has suggested its potential action on renin-angiotensin system (RAS). Objective: This study screens and explores naturally occurring bioactive constituents from the root of SMB acting on renin activity and evaluates its osteoprotective efficacy in diabetic mice. Materials and methods: Human embryonic kidney (HEK) 293 cells, engineered to express human renin, were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Twelve in vivo studies using Sprague Dawley rats, Wnt1 sw/sw mice and C57BL/6J mice were included. Kunming (KM) mice and ICR mice [ 30 , 32 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. No human studies on this topic were reported.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve in vivo studies using Sprague Dawley rats, Wnt1 sw/sw mice and C57BL/6J mice were included. Kunming (KM) mice and ICR mice [ 30 , 32 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. No human studies on this topic were reported.…”
Section: Resultsmentioning
confidence: 99%
“…For animal studies, the doses of tanshinone used were between 0.36 and 200 mg/kg [ 30 , 32 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The disease model used in these studies included retinoic acid, ovariectomy (OVX)/oestrogen deficiency, streptozocin/diabetes, lipopolysaccharide/inflammation and collagen/rheumatoid arthritis-induced bone loss, as well as polyethylene (PE) particle-induced calvarial osteolysis mimicking osteolysis in arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations